TELAAH ASB?B AL-KHAT?’ FI AL-TAFS?R (Sebab-sebab Kesalahan dalam Tafsir) - Wely Dozan (el-'Umdah, 2021)
This paper intends to explain several reasons for interpretation. The dynamics of interpretation that occurred in the first century of the emergence of Islam occurred in at least three phases: the Prophet Muhammad, the companions, and the tabi'in. The prophet's interpretation of the Qur'anic verses was not carried out thoroughly, thus leaving some empty space for the next generation, namely the companions to understand and interpret verses that were not explained by the prophet. In subsequent periods, interpretation tended to ideology as was done by the Khawarij and al-Zamakhsyari groups in al-Kasysy?f's interpretation. First, the emergence of the interpretation of the Khawarij ideology (the group that left the ranks of 'Ali) stems from the giving of the stigma of being kafir for the perpetrators of grave sins. As a consequence they deny the existence of intercession for perpetrators of grave sins based on the verses of the al-Qur'an. Second, the interpretation of al-Zamakhsyari transparently represents Mu'tazilah in certain cases, especially verses that are theological in nature.